2017
DOI: 10.5897/ajb2016.15735
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting reproductive performance of dairy cow in Algeria: Effects of clinical mastitis

Abstract: The objective of the present study was to evaluate the effects of clinical mastitis at the beginning of lactation on reproductive performance of dairy cows in Algeria. Calving to first insemination and calving to conception intervals, number of insemination per conception and conception rate at the first artificial insemination were recorded for 432 cows from 16 dairy herds in Algeria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…Nava-Trujillo et al (2010) reported that cows with CM needed 43 days more from calving to conception in comparison to clinically non-mastitis ones. Also, Bouamra et al (2017) found that cows with signs of clinical mastitis before the first insemination had greater calving to first insemination and calving to conception intervals than cows that exhibited CM after the first insemination or cows without signs of CM.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Nava-Trujillo et al (2010) reported that cows with CM needed 43 days more from calving to conception in comparison to clinically non-mastitis ones. Also, Bouamra et al (2017) found that cows with signs of clinical mastitis before the first insemination had greater calving to first insemination and calving to conception intervals than cows that exhibited CM after the first insemination or cows without signs of CM.…”
Section: Discussionmentioning
confidence: 94%
“…It significantly (P<0.05) delayed DFE, DFI and DO in both parity groups. Similarly, Bouamra et al (2017) concluded that CM had a negative effect on fertility of cows irrespective of lactation order.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mastitis, whether clinical or subclinical, results in significant economic losses due to reduced milk production, low milk content, higher culling rates, and treatment costs (Cha et al, 2011;Ali et al, 2013 andDahl et al, 2018).There is a relationship between cows suffering from mastitis and the length of the period from calving until the first ovulation reported by (Lavon et al, 2010;Nguyen et al, 2011 andGindri et al, 2019). The interval from post-partum first service and days open was longer in mastitic cows (Villa-Arcilaa et al,2017;Bouamra et al, 2017 andZigo et al,2019).In addition, lower conception rate (28-36%) recorded in mastitic cows compared to (41-42%) in healthy cows (Mellado et al, 2018and Lavon et al, 2019. May be there are limited researches on the effect of mastitis on resumption of ovarian activity and postpartum reproductive measurements in Egyptian Baladi cows.…”
Section: Introductionmentioning
confidence: 99%
“…The contrast between the genetic dairy potential of imported animals and their production was probably not only due to inadequate food intake but also the consequence of poor reproductive performance in these animals. Several studies mostly conducted in farms of Algeria have confirmed an increase in the interval between calving and conception to be 125 days [ 2 ], 130 days [ 3 ], and 147 days [ 4 ], and a decrease in conception at the first insemination of 25% [ 5 ] and 34% [ 6 ]. In these past decades, several authors have also reported lower conception rates at the first insemination and an increasing trend in the interval between calving and conception as well as services per conception in dairy cattle [ 7 - 9 ].…”
Section: Introductionmentioning
confidence: 99%